Piezo1 overexpression in the uterus contributes to myometrium contraction and inflammation-associated preterm birth - Yanmei Bi; Hao Li; Min Diao; Qian Liu; Lu Huang; Yunkai Tao; Yantong Wan; Xuemei Lin (Journal of Translational Medicine)
Abstract Background Preterm birth, a leading cause of perinatal mortality and morbidity, is often associated with inflammation and aberrant myometrial contractions. This study investigates the role of Piezo1, a mechanosensitive ion channel, in myometrium contraction and inflammation-associated preterm birth. Methods We employed Western blotting, Immunofluorescence, and Quantitative real-time PCR techniques to examine Piezo1 expression in uterine tissues. Functional assays, including myometrial contractility studies and cell contraction assays, were conducted to elucidate the effects of Piezo1 on myometrial contractions. Piezo1 inhibitors and gene knockdown techniques were used to investigate the impact of Piezo1 on inflammation-associated preterm birth, complemented by inflammatory cytokine profiling and calcium imaging to investigate the mechanism. Results Our findings reveal that Piezo1 is the predominant mechanosensitive channel in mouse myometrium tissue and mouse primary uterine smooth muscle (pUSMCs), with increased expression during mouse and human pregnancy. Following lipopolysaccharide (LPS) intrauterine injection, Piezo1 mRNA and protein levels were elevated in the mouse uterine smooth muscle layer. Direct pharmacologic activation of Piezo1 by Yoda1 increased the contraction of pUSMCs and shortened the pregnancy duration. In contrast, inhibition with Gsmtx4 or siRNA knockdown of Piezo1 attenuated LPS-induced pUSMCs contraction and spontaneous uterine myometrium contraction. Additionally, blocking or knocking down Piezo1 prolonged the pregnancy in an LPS-induced preterm birth model. Yoda1 stimulation increased intracellular Ca2+ levels in pUSMCs, while Gsmtx4 reduced these levels. Gsmtx4 decreased cox-2 expression and inflammation factors in LPS-stimulated pUSMCs. Conclusions These results suggest that Piezo1 acts as a critical regulator of uterine function, and its overexpression may predispose to preterm labor through heightened myometrial activity and inflammation. The study underscores the potential of targeting Piezo1 as a therapeutic strategy to mitigate preterm birth associated with uterine inflammation.